Use of nutritional supplements by elite Japanese track and field athletes - Shogo Tabata; Fumihiro Yamasawa; Suguru Torii; Tomohiro Manabe; Hiroshi Kamada; Akira Namba; Jo Kato; Haruka Kaneko; Keitaro Tahara; Yuka Tsukahara; Kazuki Sato (Taylor & Francis Group, 2020)
Background While scientific evidence supports the efficacy of only limited nutritional supplements (NS) on sports performance, the use of NS is widespread in athletes. Given the serious issues of health damage or unintended Anti-Doping Rule Violations due to ingestion of contaminated NS in sports, accurately understanding NS practices by athletes is crucial. This study therefore elucidated the use of NS by elite Japanese track and field (TF) athletes. Methods The subjects were 574 Japanese TF athletes, including 275 junior athletes (under 20 years) and 299 senior athletes, who participated in international competitions from 2013 to 2018. Data on NS use were collected through pre-participation medical forms obtained from all entrants before their participation in competitions. NS users were requested to report the product names and primary components of all NS they were taking. Results The overall prevalence of NS use was 63.9%. The mean number of NS products used per athlete was 1.4. The prevalence was significantly higher in women (69.2%) than in men (59.6%) (p = 0.018) and significantly higher in senior athletes (68.9%) than in junior athletes (58.9%) (p = 0.012). The prevalence of NS use was higher in long-distance runners (75.8%) and lower in jumpers (52.3%) and throwers (49.2%) than other disciplines (p < 0.001). The most prevalent components were amino acids (49.3%), followed by vitamins (48.3%), minerals (22.8%), and protein (17.8%). Conclusions Approximately two-thirds of elite Japanese TF athletes reported the use of NS, and NS practices varied by gender, age, and discipline.